An Exploratory Factor Analysis (EFA): Analysis of Message Strategy Instrument Validity - Megat Ibrahim, Nan Zakiah; Mustaffa, Che Su (Journal of Techno-Social, 2020)
Message strategy is a collection, compilation and dissemination of ideas, issues and information by taking into consideration the basics of communication skills in the execution process. In the context of development, the dissemination of information by agents of development is unclear and ambiguous which this results in the information being misunderstood by the public, especially when it involves a diversity of the publics’ backgrounds. The lack of communication strategy arrangements by the development agents has caused the information to be delayed or probably truncated for the public to accept. This paper explains the process included in identifying the items that are related to message strategy in the context of community development. The validation of the items involved two methods; content validity and factor analysis. The analysis of content validity proved that all of the items of message strategy adopted from the previous researchers in the context of development were accepted via Analysis of the Content Validity Index (CVI). In addition, factor analysis also discovered that items were extracted according to the factor as adopted from the previous instrument. Both analyses concluded that the items of message strategy which were adopted for this study in the context of community development were accepted.